PENGARUH UKURAN PERUSAHAAN, MARGIN LABA KOTOR DAN PERPUTARAN PERSEDIAAN TERHADAP PEMILIHAN METODE AKUNTANSI PERSEDIAAN PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Dewi Rejeki; Sri Wulandari (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to determine and analyze the effect of company size, gross profit margin and inventory turnover on food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. This research was conducted on the company's annual data, namely company size data, gross profit margin and inventory turnover in 2017-2019. Data analysis using logistic regression statistical test using SPSS statistical program version 25. The results of the logistic regression test or partially show that the firm size variable has no significant effect on the selection of inventory accounting methods of 0.363, gross profit margin has no significant effect on the selection of inventory accounting methods of 0.772 and inventory turnover has a significant effect on the selection of inventory accounting methods of 0.010.